(untitled) (Revista Direito em Debate, 2020)
The present study analyzes the Multiport Justice System and the performance of the Extension Project “Social Conflicts and Human Rights” of UNIJUÍ’s Law Course, focusing on the limits and possibilities of a Multiport Justice System in the context of Brazilian jurisdiction as well as whether the extension project “Social Conflicts and Human Rights” can be considered an experience in search of a Multiport Justice System. The general objective of this study is to understand the high number of "gates" of conflict resolution available in and in line with the judiciary. Initially, it studies the conflict, perceiving its diferente conceptions, whether positive or negative and the consequences arising from the several ways of understanding intersubjective conflicts. Furthermore, it analyzes the current crisis of the judiciary and the multiport system as a possible alternative to the crisis. Finally, it exposes the work done by UNIJUÍ University Extension Project called “Social Conflicts and Human Rights” as a way of applying the Multiport Justice System. In summary, it concludes that the Multiport Justice System can be an effective tool to meet the interests of the subjects in conflict from the opening of new ways to conceive the intersubjective conflicts, presenting the activities of the University Extension Project as experiences of a Multiport Justice System.